1995
DOI: 10.1038/375081a0
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of an ICE/CED-3 protease for Fas/APO-1-mediated apoptosis

Abstract: BelgiumTHE Fas/ APO-l receptor is one of the major regulators of apoptosisl-7. We report here that Fas/ APO-l-mediated apoptosis requires the activation of a new class of cysteine proteases, including interleukin-lJl-converting enzyme (ICE)s--lo, which are homologous to the product of the Caenorhabditis elegans cell-death gene ced-3 (refs 11, 12). Triggering of Fas/ APO-l rapidly stimulated the proteolytic activity of ICE. Overexpression of ICE, achieved by electroporation and microinjection, strongly potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
354
0
2

Year Published

1996
1996
2003
2003

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 589 publications
(375 citation statements)
references
References 24 publications
19
354
0
2
Order By: Relevance
“…Furthermore, caspase-8 was potently inhibited by CrmA, which is inhibitory to Fas-stimulated apoptosis of Jurkat cells though not to that induced by staurosporine . This ®nding, in combination with similarities in sensitivity to CrmA of labeled caspases in Fas-stimulated (F22, F20, F19, and F17) and staurosporine-treated (S22, S20, S19, S17) cells, is consistent with the notion that CrmA inhibition of caspase-8 is responsible for the sensitivity of Fasinduced apoptotic cell death to CrmA (Enari et al, 1995;Los et al, 1995;. Thus, caspase-8, a CrmA-sensitive protease, appears to be critical for the initiation of the protease cascade in Fasstimulated cells.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Furthermore, caspase-8 was potently inhibited by CrmA, which is inhibitory to Fas-stimulated apoptosis of Jurkat cells though not to that induced by staurosporine . This ®nding, in combination with similarities in sensitivity to CrmA of labeled caspases in Fas-stimulated (F22, F20, F19, and F17) and staurosporine-treated (S22, S20, S19, S17) cells, is consistent with the notion that CrmA inhibition of caspase-8 is responsible for the sensitivity of Fasinduced apoptotic cell death to CrmA (Enari et al, 1995;Los et al, 1995;. Thus, caspase-8, a CrmA-sensitive protease, appears to be critical for the initiation of the protease cascade in Fasstimulated cells.…”
Section: Discussionsupporting
confidence: 86%
“…In particular, we show that the addition of active caspase-8 (MACH/FLICE/Mch5) to extracts from non-apoptotic Jurkat cells can trigger stepwise activation of caspases that is strikingly similar to that induced by Fas stimulation. Finally, we ®nd that caspase-8 is sensitive to CrmA, the inhibitor of Fasinduced apoptotic cell death (Enari et al, 1995;Los et al, 1995;. Taken together, these results support the notion that the activation of multiple caspases is required for the organization of protease cascades as well as for the cleavage of multiple apoptosis-associated substrates.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…Decreased surface expression of CD95 has been reported to confer resistance to CD95-induced cell death. 34 Engagement of CD95 receptor on the surface leads to the activation of procaspase 8, caspase 3, 35 and ultimately to cleavage of the caspase 3 substrate poly (ADP-ribose) polymerase (PARP). 36 To determine whether higher resistance to anti-CD95-induced cell death in c-Myc-deficient cells correlated with changes in PARP processing, we performed Western blot analysis on these cells.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that Fas-and tumor necrosis factor (TNF) receptor-mediated apoptosis is driven by caspase family, because it is suppressed by their inhibitors, including cowpox virus CrmA Enari et al, 1995;Los et al, 1995), baculovirus p35 and tetrapeptide caspase-1 and caspase-3 inhibitors (Enari et al, 1995;Los et al, 1995;Schlegel et al, 1996;Chinnaiyan et al, 1996;Hasegawa et al, 1996). It has also been reported that thymocytes from caspase-1-de®cient mice are resistant to Fas-mediated apoptosis, indicating the direct involvement of caspase-1 itself in this process of thymocyte death (Kuida et al, 1995).…”
Section: Introductionmentioning
confidence: 99%